How to integrate screening for cervical cancer into grassroots health services for low income countries: An implementation research. (2nd October 2021) - Nguyen, Ngan T. K.; Nguyen, Linh T.; Le, Hoang T.; Nguyen, Binh T.; Pham, Nha Ba; Pham, Phuong Lan; Vu, Lan T. H.
ABSTRACT: This implementation research examines the feasibility of training health care workers at grassroot level in Vietnam to perform visual inspection with acetic acid as a regular screening service for cervical cancer at commune health stations (CHSs). Employing a two-phase design, the study trained 36 nurses working at CHSs to do VIA screening method in the first phase. In the second phase, evaluation on the capacity of those trained to do VIA method as well as client's satisfaction with VIA services performed in CHSs setting was done among 380 clients. Results indicated that within a short time, CHS nurses can be trained to perform VIA correctly (80.6% felt confident to perform VIA and 75% was able to perform test efficiently). All clients showed high level of satisfaction with VIA services provided at CHS setting. This implementation research provided evidences that VIA screening services performed by local midwives/nurses at grassroots level can be an optimal solution to deal with both the raising burden of cervical cancer and the current concern of shortage of well-trained doctors in low resource setting areas. It also gave some important lessons for health care managers on how to sufficiently integrate cervical cancer screening in low resource settings.